A novel process for the biological detoxification of non-metal residue from waste copper clad laminate treatment: From lab to pilot scale. (10th May 2020) - Zhou, Wenbo; Chen, Yanzhi; Cheng, Haina; Liu, Xiaowen; Tian, Zhuang; Zhang, Lijuan; Kang, Xin; Ge, Yang; Peng, Jing; Sun, Jianxing; Wen, Yong; Wang, Wei; et al.
Abstract: A new process of biological detoxification and comprehensive utilization of non-metal residue from waste copper clad laminates treatment was proposed. The process mainly includes microbial cultivation, bioleaching, metal recovery, and wastewater treatment. The leaching rate of metal by bioleaching in acidic environment with pH1.0–2.0 was close to 100% and was 8.7% higher than that by dilute sulfuric acid leaching, and about 11.4% higher than that by circulating tailings leaching. Through a series of continuous batch operation, it was found that Eh (Oxidation/Reduction Potential), pH, c (Cu 2+ ), c (TFe, total iron) of solutions in each section fluctuated within the expected range. Although the concentration of accumulated iron ions in the solution exceeds 20 g/L, the concentration of planktonic microorganisms was still above 6 × 10 7  cells/mL, and the activated microbial solution still had a good leaching effect on metals in the waste. The residue directly obtained through a filter press had a water content of less than 30%, while that dried residue has a copper content of less than 524 mg/kg. In addition, the grade of sponge copper prepared in the replacement section could reach 86.63%, and the direct yield of copper can reach more than 90%. Furthermore, an economic analysis mainly based on material balance had further confirmed the feasibility of the green treatment process. Graphical abstract: Strategies for detoxification and utilization of non-metal residue from waste CCL residue treatment. Image 1 Highlights: Bioleaching of electronic waste for detoxification was achieved in pilot scale. Bio-cultivation, copper cementation and water treatment form an innovative process. The coupling process of bio-detoxification and metal recycling was demonstrated. Linkage experiment showed economically feasible for electronic waste treatment.